2020
DOI: 10.5430/ijhe.v9n2p156
|View full text |Cite
|
Sign up to set email alerts
|

Instructional Practices of Part-Time Faculty at Two-Year Institutions: Observations and Implications

Abstract: This paper attempts to shed more light on the teaching practices of part-time faculty members and their impacts on community college students. It has been found that part-time faculty members employ traditional teaching practices compared to full-time faculty members. These teaching practices have, to varying degrees, negative effects on community college students. It has also been found that some of the compelling factors that hinder part-time faculty from utilizing effective teaching practices are institutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Alternatively, other explanations, such as pedagogical differences and differential student exposures to teacher typologies, may be driving our findings regarding faculty employment status at California community colleges. Alshehri (2020) found that parttime faculty employed at 2-year colleges were likelier to use traditional, lecture-style pedagogy than their full-time counterparts. Also, prepared and economically advantaged students, compared to unprepared and economically disadvantaged students, are likely to get different exposure rates to part and full-time faculty depending on who is more likely to be chosen to teach remedial courses or courses that meet in non-traditional times or online/hybrid (Barhoum, 2018).…”
Section: Full-time Faculty Concentrations Improve Outcomes For the Hi...mentioning
confidence: 96%
“…Alternatively, other explanations, such as pedagogical differences and differential student exposures to teacher typologies, may be driving our findings regarding faculty employment status at California community colleges. Alshehri (2020) found that parttime faculty employed at 2-year colleges were likelier to use traditional, lecture-style pedagogy than their full-time counterparts. Also, prepared and economically advantaged students, compared to unprepared and economically disadvantaged students, are likely to get different exposure rates to part and full-time faculty depending on who is more likely to be chosen to teach remedial courses or courses that meet in non-traditional times or online/hybrid (Barhoum, 2018).…”
Section: Full-time Faculty Concentrations Improve Outcomes For the Hi...mentioning
confidence: 96%
“…Community colleges typically serve a larger proportion of the nation's at-risk student population compared to traditional 4-year universities and account for more than one-half of all undergraduate enrollment in the United States (Bailey et al, 2015;CCCSE 2016;Mellow et al, 2011;Shugart, 2016;USDoE, 2023a-d). Students at 2-year intuitions and at-risk students are more likely to be successful when faculty use learner-centered principles and technology (Alshehri, 2020;APA, 1997;Vygotsky, 1978). In 1996, Chickering and Ehrmann stated that active learning and technology were critical to the "seven principles" (Chickering & Gamson, 1987) of quality undergraduate education that include active learning and tight feedback loops.…”
Section: The 2-year Public College Landscape In the United Statesmentioning
confidence: 99%
“…Community colleges that prioritize learning-centered practices across disciplines ensure that new faculty members are aligned with their approaches during the hiring process (Wyner, 2014, p. 85). These factors highlight the importance of incorporating learner-centered pedagogical knowledge (PK) and technological knowledge (TK) into the KSAs needed in community college faculty for effective teaching (e.g., Alshehri, 2020;Levin et al, 2006;Novita et al, 2022;Wyner, 2014).…”
Section: Community College Faculty Knowledge Skills and Abilitiesmentioning
confidence: 99%
See 1 more Smart Citation